2009
DOI: 10.1038/nmeth.1292
|View full text |Cite
|
Sign up to set email alerts
|

Genetically timed, activity-sensor and rainbow transsynaptic viral tools

Abstract: We developed retrograde, transsynaptic pseudorabies viruses (PRVs) with genetically encoded activity sensors that optically report the activity of connected neurons among spatially intermingled neurons in the brain. Next we engineered PRVs to express two differentially colored fluorescent proteins in a time-shifted manner to define a time period early after infection to investigate neural activity. Finally we used multiple-colored PRVs to differentiate and dissect the complex architecture of brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 18 publications
1
85
0
1
Order By: Relevance
“…The ability of neurotropic viruses to replicate and spread through neural circuits has brought a polysynaptic perspective to circuit analysis (2-6). Recent genetic engineering of such viruses has produced increasingly powerful probes that have provided novel insights into the identity, organization, and activity of neural networks in a variety of systems (7)(8)(9).…”
mentioning
confidence: 99%
“…The ability of neurotropic viruses to replicate and spread through neural circuits has brought a polysynaptic perspective to circuit analysis (2-6). Recent genetic engineering of such viruses has produced increasingly powerful probes that have provided novel insights into the identity, organization, and activity of neural networks in a variety of systems (7)(8)(9).…”
mentioning
confidence: 99%
“…Several previous reports have been successful in construction of PRVs for delivering foreign genes to neurons [35]. PRV is an especially important tool for labelling neuronal circuits [36], which was combined with delivery of activity markers to labelled neurons [37]. Application of PRV-based gene transfer vectors in the cardiovascular research field has not yet been reported.…”
Section: Gene Transfer Techniques: Advantages and Limitationsmentioning
confidence: 99%
“…Because of these drawbacks it is not recommended to use alpha-herpesviruses in higher doses and for longer time period [56]. Earlier, another problem was the bidirectional spreading, but today certain modified strains has the advantage of unidirectional transfer [50,57].In contrast, rabies does not change neuronal metabolism,…”
Section: Virusesmentioning
confidence: 99%